Effect of Sodium Butyrate on Growth Performance of Dairy Calves: An Overview - Arya, Anjali; Lunagariya, Pravinchandra Mohan; Trivedi, Manojkumar Motibhai; Modi, Rakeshkumar Jayantilal; Patel, Yogeshkumar Gulabbhai; Sorathiya, Kalpeshkumar Keshubhai (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Butyrate, a Volatile Fatty Acids (VFAs) is produced by microbial fermentation of feed carbohydrates in the stomach and large intestine. Butyrate is the least prevalent of the three main VFAs produced in the gastrointestinal tract (acetate, propionate, and butyrate), however, has the most dynamic behaviour and functions in growing calves. It is essential for promoting the growth of the various rumen, abomasum, and intestinal epithelia. Dietary butyrate supplementation can help to further speed up the growth of the gastrointestinal tract (GIT). There is proof that adding Na-butyrate to liquid feed at a higher dose rate of 45 g per day improved growth performance, feed efficiency, and antioxidant activity in dairy calves. It has been frequently demonstrated that adding sodium butyrate to a liquid diet at a modest level (0.3 percent of DM) will enhance pre-weaned calves' growth, function, and GIT development and is also advisable due to a very strong, unpleasant smell. Future research should concentrate on how well Na-butyrate works to improve the growth performance of calves in Indian environments.
Keywords: Butyrate; Dairy calves; Gastrointestinal tracT; Volatile fatty acids